Grand Design of Halal Supply Chain on Pesantren Business: Study on AMIDAS Manufacturer's Company - Retnowati, May Shinta; Arjuna, Agma; Al Faruqi, Musta’an; Hidayat, Iman Nur; Diana, Rashda (University of Darusssalam Gontor, 2023)
Indonesia is still far behind the western countries that have started a lot of studies on the halal business sector. Whereas on the one hand Indonesia is a country with a majority of Muslims, thus obliging most of them to meet their needs with the halal sector. Besides, Indonesia also has many pesantren that become a halal ecosystem indirectly. Many pesantren to meet their needs through various business units that indirectly support and improve the market sector halal in Indonesia. One of the business unit to be studied is a mineral water production business unit named AMIDAS. This research method uses qualitative research. Data collection techniques through observation, interviews, and documentation, with inductive descriptive analysis model to put forward the design form of halal supply chain implemented in AMIDAS manufacturer company. The results, as a manufacturer, AMIDAS goes through the whole supply chain procedure. AMIDAS receives plastic bottles, gallons, cartons, and cups from material suppliers from different regions for which they have also had security licenses on the products they produce. Products are received from suppliers by manufacturing, which then stores them in warehouses before producing bottled water for the corporation. AMIDAS distributes the goods to retailer, sub-retailer, and so on after it is completed and ready for marketing. The product is stored in a clean warehouse and is protected from unclean or unwanted goods, as well as transportation used as well customers purchase goods from retailers after they are resold to sub-retailers dispersed throughout the Ponorogo region and surrounding Javan cities.